Career and Family Dilemmas: Uncovering the Work-family conflict Relationship with Job Satisfaction - Dwi Nova Nauli, Made; Angelita Hulu, Stefany; Yusliza Surbakti, Nursyadiva; Manurung, Wilda; Hartini, Sri; Elvinawanty, Rianda; Atrizka, Diny (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Work-family conflict has been a significant challenge for workers, especially women who have dual responsibilities in both work and family. This conflict negatively impacted job satisfaction, which ultimately affected employee performance and well-being. This study aimed to analyze the relationship between work-family conflict and job satisfaction among female DPRD members in Nias. The research employed a quantitative approach using Pearson correlation and partial correlation analysis to examine the relationships between variables. The findings revealed a significant negative relationship between work-family conflict and job satisfaction, indicating that higher levels of conflict led to lower job satisfaction. Time-Based Conflict had the most substantial influence on aspects such as supervision, relationships with colleagues, and workload. Additionally, the study found that work-family conflict contributed 23.1% to the variability in job satisfaction. The implications of this study suggested the necessity for organizational policies that support work-life balance, such as flexible working arrangements and social support for female employees. With more adaptive policies, organizations could enhance employee well-being and work effectiveness, creating a more productive and harmonious work environment.Work-family conflict menjadi tantangan signifikan bagi pekerja, terutama perempuan yang memiliki tanggung jawab ganda dalam pekerjaan dan keluarga. Konflik ini dapat berdampak negatif terhadap kepuasan kerja, yang pada akhirnya mempengaruhi kinerja dan kesejahteraan pekerja. Penelitian ini bertujuan untuk menganalisis hubungan antara work-family conflict dan kepuasan kerja pada anggota DPRD perempuan di Nias. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan teknik analisis korelasi Pearson dan korelasi parsial untuk menguji hubungan antar variabel. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara work-family conflict dan kepuasan kerja, di mana semakin tinggi konflik yang dialami, semakin rendah tingkat kepuasan kerja. Time-Based Conflict memiliki pengaruh terbesar terhadap aspek supervisi atasan, hubungan dengan rekan kerja, dan beban pekerjaan. Selain itu, hasil penelitian juga menunjukkan bahwa work-family conflict berkontribusi sebesar 23.1% terhadap variabilitas kepuasan kerja. Implikasi dari penelitian ini adalah perlunya kebijakan organisasi yang mendukung keseimbangan kerja-keluarga, seperti fleksibilitas kerja dan dukungan sosial bagi pekerja perempuan. Dengan kebijakan yang lebih adaptif, organisasi dapat meningkatkan kesejahteraan pekerja dan efektivitas kerja, sehingga menciptakan lingkungan kerja yang lebih produktif dan harmonis.